2017
DOI: 10.1167/iovs.17-22219
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Myopia on Corneal Biomechanics in Glaucoma and Nonglaucoma Patients

Abstract: PurposeWe evaluated the impact of myopia on corneal biomechanical properties in primary open-angle glaucoma (POAG) and nonglaucoma patients, and the effect of modification of glaucoma on myopic eyes.MethodsThis cross-sectional study included 66 POAG eyes (33 myopia, 33 nonmyopia) and 66 normal eyes (33 myopia, 33 nonmyopia). Seven corneal biomechanical parameters were measured by ultra-high-speed Scheimpflug imaging, including corneal deformation amplitude (CDA), inward/outward corneal applanation length (ICA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 32 publications
0
40
1
Order By: Relevance
“…Chang’s study pointed out that the axial elongation led to corneal flattening and thickness reduction [ 35 ], suggesting that the increase of axial length may affect the biomechanics of the cornea and previous studies have proved this. Myopia in glaucoma and normal eyes would lead to biomechanical parameters changes such as corneal deformation amplitude (CDA), outward corneal applanation (OCA) and cornea stiffness (CS) [ 36 , 37 ]. Especially the cornea in high myopia had faster outward corneal velocity (OCV) and higher CDA compared to emmetropia [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chang’s study pointed out that the axial elongation led to corneal flattening and thickness reduction [ 35 ], suggesting that the increase of axial length may affect the biomechanics of the cornea and previous studies have proved this. Myopia in glaucoma and normal eyes would lead to biomechanical parameters changes such as corneal deformation amplitude (CDA), outward corneal applanation (OCA) and cornea stiffness (CS) [ 36 , 37 ]. Especially the cornea in high myopia had faster outward corneal velocity (OCV) and higher CDA compared to emmetropia [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the refractive error associated with myopia comes from the axial length, it is increasingly recognised that changes of the anterior segment in high myopia lead to significant optical and higher order aberrations 60. A potentially interesting aspect is the study of biomechanical changes associated with corneal thickness in high myopia, which may affect the evaluation of intraocular pressure61 and diagnosis of glaucoma—elaborated further later in this review 62. However, current studies have variable results due to the different imaging techniques and the technological limitations in measuring on the biomechanical changes of the cornea associated with increasing myopia 63…”
Section: Introductionmentioning
confidence: 94%
“…16,22 For example, most prior studies included glaucoma patients with high baseline 18,19 or relatively high treated IOP. 16,17,22 In a previous study, we demonstrated the greater compliance of glaucoma eyes compared with healthy eyes after controlling for these confounding effects. 23 However, because most previous studies, including ours, enrolled glaucoma patients under medical treatment, the question remains unanswered as to whether biomechanical alterations in glaucoma eyes were caused by glaucoma per se, medications for glaucoma, or both.…”
mentioning
confidence: 99%